Three-dimensionally ordered macro-microporous metal organic frameworks with strong sulfur immobilization and catalyzation for high-performance lithium-sulfur batteries. (June 2020) - Cui, Guoliang; Li, Gaoran; Luo, Dan; Zhang, Yongguang; Zhao, Yan; Wang, Daorui; Wang, Jiayi; Zhang, Zhen; Wang, Xin; Chen, Zhongwei
Abstract: Lithium-sulfur (Li–S) batteries have been recognized as one of the most promising technologies for next-generation energy storage. However, their practical implementation is greatly impeded by the sluggish sulfur kinetics and unsatisfactory cyclability. Herein, a novel three-dimensionally ordered macro-microporous metal organic frameworks (3DOM ZIF-8) is developed via self-templated coordination-replication method, which serves as an advanced sulfur reservoir for enhanced Li–S battery performance. The unique hierarchical architecture not only facilitates the electrolyte infiltration and ion/mass transportation, but also increases the surface area for abundant exposure of active interfaces. Moreover, the nanometric ZIF-8 subunits impose strong sulfur immobilization and catalyzation through their chemical interactions with polysulfides, thus rendering significantly inhibited shuttle effect and fast reaction kinetics. Benefiting from these synergistic features, sulfur electrodes based on 3DOM ZIF-8 exhibit excellent electrochemical performance, i.e., prolonged cycling stability with a low capacity decay of 0.028% per cycle over 500 cycles, as well as high areal capacity and decent cyclability under raised sulfur loading and limited electrolyte, demonstrating a great promise in developing practically viable Li–S batteries. Graphical abstract: A hierarchical macro-microporous 3DOM ZIF-8 has been developed as advanced sulfur host materials. The unique architecture and strong chemical interactions with lithium polysulfides enable expedite ion/mass transfer, potent sulfur confinement, and effective conversion catalyzation toward fast and durable Li–S batteries. Image 1 Highlights: 3DOM ZIF-8 was prepared via a self-templated coordination-replication method. 3DOM ZIF-8 integrates macroporous and microporous features in ordered architecture. 3DOM ZIF-8 as sulfur host imposes strong sulfur confinement and catalyzation. S/3DOM ZIF-8 electrodes deliver prolonged cyclability and enhanced rate capability.